DUALISME YURISDIKSI DALAM PENYELESAIAN KERUGIAN KEUANGAN NEGARA: KONSEP INTEGRATIF TERHADAP PENEGAKAN HUKUM TIPIKOR - Andrian, Zulkifli (Faculty of Law, Universitas Tanjungpura, 2026)
Abstract The eradication of corruption in Indonesia faces a dualism of jurisdiction between administrative law and criminal law in addressing state financial losses. The friction between these two legal regimes, particularly concerning the offense of abuse of authority, has generated legal uncertainty and fostered the phenomenon of policy criminalization, thereby hindering effective governance. This study employs normative legal research aimed at analyzing this dualism and formulating an integrative concept for the enforcement of corruption law. The analysis demonstrates that Constitutional Court Decision No. 25/PUU-XIV/2016 constitutes a critical turning point by transforming the offense of state financial loss into a material offense and affirming the necessity of proving malicious intent (mens rea) to distinguish administrative violations (maladministration) from corruption offenses. To reconcile this contradiction, the study proposes a Conditional Priority Model as an integrative framework. This model requires that any alleged state financial loss be subjected to prior administrative review by the Government Internal Supervisory Apparatus (APIP) and the Administrative Court (PTUN) as an entry gate. Escalation to criminal proceedings may occur only under specific conditions, namely where strong indications of mens rea are found, where other criminal offenses coexist, or where there is non-compliance with administrative sanctions. This concept is expected to enhance legal certainty, protect public officials from unjust criminalization, and focus law enforcement resources on genuine acts of corruption. Abstrak Pemberantasan korupsi di Indonesia dihadapkan pada dualisme yurisdiksi antara hukum administrasi negara (HAN) dan hukum pidana dalam penyelesaian kerugian keuangan negara. Friksi antara dua rezim hukum ini, khususnya terkait delik penyalahgunaan wewenang, telah menimbulkan ketidakpastian hukum dan fenomena kriminalisasi kebijakan yang menghambat jalannya pemerintahan. Penelitian ini menggunakan hukum normatif dengan bertujuan untuk menganalisis dualisme tersebut dan merumuskan sebuah konsep integratif dalam penegakan hukum tindak pidana korupsi. Hasil analisis menunjukkan bahwa Putusan Mahkamah Konstitusi No. 25/PUU-XIV/2016 menjadi titik balik penting dengan mengubah delik korupsi menjadi delik materiil dan menegaskan pentingnya pembuktian niat jahat (mens rea) untuk membedakan antara pelanggaran administratif (maladministrasi) dengan tindak pidana korupsi. Untuk mendamaikan kontradiksi ini, penelitian merekomendasikan sebuah Model Prioritas Bersyarat (Conditional Priority Model) sebagai konsep integratif. Model ini mengusulkan agar setiap dugaan kerugian negara wajib melalui pengujian administratif oleh APIP dan PTUN terlebih dahulu sebagai pintu masuk. Eskalasi ke proses pidana hanya dapat dilakukan secara bersyarat, yakni jika ditemukan indikasi kuat adanya mens rea, adanya delik lain yang menyertai, atau ketidakpatuhan terhadap sanksi administratif. Konsep ini diharapkan dapat menciptakan kepastian hukum, melindungi pejabat dari kriminalisasi, dan memfokuskan sumber daya penegakan hukum pada korupsi yang sesungguhnya.